Attention and Functional Connectivity Among Patients With Early-Stage Subcortical Ischemic Vascular Disease and Alzheimer’s Disease - Tu, Min-Chien; Hsu, Yen-Hsuan; Yang, Jir-Jei; Huang, Wen-Hui; Deng, Jie Fu; Lin, Shih-Yen; Lin, Chien-Yuan; Kuo, Li-Wei (Frontiers in Aging Neuroscience, 2020)
The current study compared attention profiles and functional connectivity of frontal regions in patients with early-stage subcortical ischemic vascular disease (SIVD) and Alzheimer’s disease (AD). Twenty patients with SIVD, 32 patients with AD, and 24 subjects with normal cognition (NC) received cognition and resting-state functional magnetic resonance imaging (rs-fMRI) evaluations. The Cognitive Abilities Screening Instrument was used to assess global cognition, and simple attention, processing speed, divided attention, and vigilance/sustained attention were evaluated using the Digit Span Forward, Trail Making Test, Symbol Digit Modality Test, and Conners Continuous Performance Test, respectively. Voxel-based regional homogeneity (ReHo) derived from rs-fMRI data was analyzed to identify significant clusters, which were further correlated with attention profiles. While the patients with SIVD and AD had comparable global cognitive ability, those with SIVD exhibited worse divided attention and vigilance/sustained attention than those with AD. Compared to the NC group, the patients with SIVD exhibited decreased ReHo within the right middle frontal gyrus and left anterior cingulate gyrus, whilst the patients with AD exhibited increased ReHo within the right orbital part of frontal regions. Correlations between these three clusters with attention exhibited distinct patterns according to the dementia subtype, as did attention indices with significance in predicting global cognition. In summary, our study suggested that worse attention performance was associated with functional disconnection within the frontal regions among patients with SIVD than in those with AD. Frontal functional disconnection may underlie the pathogenesis responsible for defective divided attention, vigilance/sustained attention, and notable within-group variations identified in SIVD.